Efforts to Achieve Sustainable Development Goals (SDGs) at the Village Level: A Case Study of Cibadak Village, Sukamakmur Subdistrict, Bogor Regency, West Java, Indonesia - Nurhayati Nurhayati; Muhammad Hizbu Hakim; Aurelia Atha Hapsari; Wafa Zabitha Jhonaidi; Rahel Pardosi; Delfia Dita Syifa; Dewinta Shifa Labibah; Nabila Ayufahra Sabita (CV. AFDIFAL MAJU BERKAH, 2024)
This article explores the implementation of the KUM-ITT program in Cibadak Village, Sukabumi, West Java. The program addressed critical community challenges, including access to clean water and healthcare infrastructure, by engaging stakeholders through a pentahelix approach. The activities included health education, stunting prevention, and lifestyle guidance. The outcomes showed improved public awareness and access to healthcare resources, aligning with SDGs such as poverty alleviation, quality education, and sustainable community development